Diagnosis of alpha-1-antitrypsin deficiency by DNA analysis of children with liver disease - De TOMMASO,Adriana Maria Alves (2001)
Background - Alpha-1-antitrypsin deficiency is a genetic disorder which is transmitted in a co-dominant, autosomal form. Alpha-1-antitrypsin deficiency affects mainly the lungs and the liver leading, in the latter case, to neonatal cholestasis, chronic hepatitis or cirrhosis. A precise diagnosis of Alpha-1-antitrypsin deficiency may be obtained by biochemical or molecular analysis. Objective - The purpose of this study was to use DNA analysis to examine the presence of an alpha-1-antitrypsin deficiency in 12 children suspected of having this deficiency and who showed laboratory and clinical characteristics of the disease. Patients and Methods - Twelve patients, aged 3 months to 19 years, who had serum alpha-1-antitrypsin levels lower than normal and/or had hepatic disease of undefined etiology were studied. The mutant alleles S and Z of the alpha-1-antitrypsin gene were investigated in the 12 children. Alpha-1-antitrypsin gene organization was analyzed by amplification of genoma through the polymerase chain reaction and digestion with the restriction enzymes Xmnl (S allele) and Taq 1 (Z allele). Results - Seven of the 12 patients had chronic liver disease of undefined etiology and the other five patients had low serum levels of alpha-1-antitrypsin as well as a diagnosis of neonatal cholestasis and/or chronic liver disease of undefined etiology. Five of the 12 patients were homozygous for the Z allele (ZZ) and two had the S allele with another allele (*S) different from Z. Conclusion - These results show that alpha-1-antitrypsin deficiency is relatively frequent in children with chronic hepatic disease of undefined etiology and/or low alpha-1-antitrypsin levels (41.6%). A correct diagnosis is important for effective clinical follow-up and for genetic counseling.